THE EVOLVING ROLE OF TEACHERS IN AI-ENHANCED CLASSROOMS: CHALLENGES AND OPPORTUNITIES - Nurjana Cyntia Rahman; Som Chai; Said Subhan Posangi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2026)
The integration of Artificial Intelligence (AI) in education is reshaping the traditional role of teachers, introducing both opportunities and challenges. AI-powered tools, including adaptive learning systems and automated assessments, are becoming integral to modern classrooms, promising personalized learning experiences and enhanced classroom management. However, these technological advancements also require teachers to adapt to new responsibilities and redefine their pedagogical practices. This study explores the evolving role of teachers in AI-enhanced classrooms, focusing on how AI affects their professional identity, teaching strategies, and relationships with students. The research employs a mixed-methods approach, combining surveys, semi-structured interviews, and classroom observations across ten institutions that have implemented AI tools. The findings reveal that while AI improves student engagement and administrative efficiency, teachers face challenges in maintaining the human aspect of education, such as fostering emotional intelligence and teacher-student interactions. The study concludes that AI can enhance pedagogical practices if properly integrated, but it requires teachers to embrace new technologies while retaining the core human-centered values of education. The research highlights the need for professional development and institutional support to help educators navigate this transition effectively.